Evaluation of students’ environmental attitude instruments: exploratory and confirmatory factor analysis - Siti Nurul Izzah; Sudarmin Sudarmin; Wiyanto Wiyanto; Sri Wardani (International Journal of Evaluation and Research in Education (IJERE), 2024)
One’s environmental attitude can predict human behavior toward the environment. This study aimed to validate the environmental attitude instrument with the science, technology, engineering, and mathematics in ethnoscience-integrated (Ethno-STEM) approach. The questionnaire consisted of 16 items and was tested on 159 eighth-grade students. Data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The communality value of three instrument items was less than 0.5, so they were excluded in EFA stage 1. The EFA stage 2 test results showed that the 13 instrument items had a factor loading of more than 0.5 and were categorized into five factors. The CFA stage 1 was conducted using linear structural relations (LISREL) and obtained thet-value for all items in factors 1-4 more than the t-table, so they were declared valid. Factor 5 was omitted in CFA test stage 2 due to invalid items. The CFA test results showed that the t-count of the four factors was more than the t-table. Based on the goodness of fit value, the model and measurement matrices were the same (model fit). Thus, the environmental attitude instrument items are declared valid, and the model is fit. The instrument can be used to measure environmental attitudes.